Efficacy of Percutaneous Nephrolithotomy in the Treatment of Renal Calculi of 10 to 20 MM Size: A Comparison With Extracorporeal Shock Wave Lithotripsy - Alam, Muhammad Mahmud; Karim, Mohammad Rezaul; Khan, Mohammad Ohiduzzaman; Rahman, Mohammad Mukhlesur; Asma, Mahfuja; Islam, AKM Anwarul (Bangladesh Journal of Urology, 2020)
Background: Stones in the urinary tract is a common medical problem in the general population. At present, the great expansion in minimally invasive techniques has led to the decrease in open surgery. Extracorporeal shock wave lithotripsy (ESWL) has been introduced as an alternative approach which disintegrates stones in the kidney and upper urinary tract through the use of shock waves. Nevertheless, as there are limitations with the success rate in ESWL, other minimally invasive modalities for kidney stones such as percutaneous nephrolithotomy (PCNL) is also widely applied. There is a trend of using ESWL for treatment of renal stones smaller than 1 cm and PCNL in those with stones greater than 2 cm. Nevertheless, no consensus regarding treatment of renal stones between 1 to 2 cm stones. The objective of this prospective study was to compare the results of ESWL and PCNL for treatment of 1 to 2 cm renal stones. Method : This is a quasi experimental study. This study was conducted to compare the efficacy and safety of percutaneous nephrolithotomy (PCNL) and extracorporeal shock wave lithotripsy (ESWL) in treating 10 to 20 mm sized renal stone among the Bangladeshi population. This prospective study conducted between the periods of September, 2011 to August, 2012 in the department of urology, Bangabandhu Sheikh Mujib medical university (BSMMU) Hospital. All the patients attending the urology outpatient clinic with 10 to 20mm renal calculi were the study population. A total of 70 subjects were enrolled for this study and they were equally divided into two groups so that each group had 35 subjects. The one group received PCNL whereas the other group received ESWL. Statistical analyses of the results were obtained by using window based computer software devised with Statistical Packages for Social Sciences (SPSS-15). Results: There is no statistically significant difference in regarding age, sex, stone side(lt. or rt.), the distribution of stone (upper, middle and lower calyx) and size between the groups (p>0.05). At 3 month follow up among the patients in ESWL group stone cleared and not cleared were 25(71.4%) and 10(28.6%) respectively and at 3 month follow up among the patients in PCNL group stone cleared and not cleared were 33(94.3%) and 2(5.7%)respectively. There is statistically significant difference in stone clearance rate at 3 month follow up between the groups (p<0.05). All patients in ESWL group developed post procedure haematuria 35(100.0%). Other post procedure complications among the ESWL group pain, fever and steinstrasse were 12(34.3%), 07(20.0%) and 03(08.6%) respectively. Common post procedure complications among the patients of PCNL group pain, haematuria and fever were 11(31.4%), 33(94.3%) and 13(37.1%) respectively. Other post procedure complications in PCNL group were vomiting (8.6%), urinary leakage (5.7%), wound infection (11.4%) and urinary cutaneous fistula (5.7%). There was no statistically significant difference post procedure pain, haematuria and fever between the groups (p>0.05), but statistically significant difference observed in steinstrasse and wound infection between the groups (p<0.05). Mean±SD of hospital stay among the patients of ESWL group and PCNL group was 1.37±0.65 and 4.34±1.43 days respectively. There is statistically significant difference in hospital stay between the groups (p<0.05). Conclusion: Though some specific complications which can be treated conservatively are more in PCNL group it may be concluded that the treatment with PCNL is better option than ESWL among the patients having renal calculi 10 to 20 mm. Bangladesh Journal of Urology, Vol. 21, No. 2, July 2018 p.98-104